Effect of synbiotic dietary supplementation on survival, growth performance, and digestive enzyme activities of common carp (Cyprinus carpio) fingerlings - P. Ghasempour Dehaghani; M. Javaheri Baboli; A. Taghavi Moghadam; S. Ziaei-Nejad; M. Pourfarhadi (Czech Journal of Animal Science, 2015)
Effects of different levels of Biomin® IMBO synbiotic, including Enterococcus faecium (as probio-tic), and fructooligosaccharides (as prebiotic) on survival, growth performance, and digestive enzyme activities of common carp fingerlings (Cyprinus carpio) were evaluated. The experiment was carried out in four treatments (each with 3 replicates), including T1 = control with non-synbiotic diet, T2 = 0.5 g/kg synbiotic diet, T3 = 1 g/kg synbiotic diet, and T4 = 1.5 g/kg synbiotic diet. In total 300 fish with an average weight of 10 ± 1 g were distributed in 12 tanks (25 animals per 300 l) and were fed experimental diets over a period of 60 days. The results showed that synbiotic could significantly enhance growth parameters (weight gain, length gain, specific growth rate, percentage weight gain) (P < 0.05), but did not exhibit any effect on survival rate (P > 0.05) compared with the control. An assay of the digestive enzyme activities demonstrated that the trypsin and chymotrypsin activities of synbiotic groups were considerably increased than those in the control (P < 0.05), but there was no significant difference in the levels of α-amylase, lipase, or alkaline phosphatase (P > 0.05). This study indicated that different levels of synbiotic have the capability to enhance probiotic substitution, to improve digestive enzyme activity which leads to digestive system efficiency, and finally to increase growth. It seems that the studied synbiotic could serve as a good diet supplement for common carp cultures.